SOSIALISASI KONSERVASI LAHAN GAMBUT DAN PERTANIAN TANPA BAKAR DI DESA LIMBUNG, KABUPATEN KUBU RAYA - Putri Yuli Utami; Muhammad Iwan; Apri Rahmadi; Eko Julianto (Universitas Mataram, 2023)
Droughts caused by long droughts can cause fires on peatlands. Peatlands have a major function for the ecosystem, which is efficient in absorbing carbon and is a habitat for a variety of flora and fauna. However, this is not yet understood by the community, because in the dry season land clearing is often done by burning. Limbung Village is one of the villages in Sungai Raya Sub-District, Kubu Raya Regency. This PKM aims to provide socialization related to peatland conservation and agriculture without burning, to provide knowledge of peatland conservation, peatland functions, conservation benefits, and agricultural techniques without burning. The method of this socialization activity is lecture and question and answer. The socialization activities were conducted through lectures given by resource persons related to peatland conservation and no-burn agriculture. A pre-test was conducted before the activity started and a post-test was given to the participants at the end. Based on the results of the participants' questionnaires before participating in the socialization activities and after participating in the socialization activities, there was an increase in knowledge. The value of the participants' pre-test results before the socialization activity was 7.5% and the value of the participants' post-test results after participating in the socialization activity was 97.5%. These results show a 90% increase in participants' knowledge after participating in the socialization activity on peatland conservation and no-burn agriculture. The participants were very sympathetic and enthusiastic while listening to the materials and asking questions to the resource person. The socialization activity on peatland conservation and no-burn agriculture went well because it was supported by village officials, farmer groups, and the community.